Doenças e manifestações psicossomáticas na infância e naadolescência: construindo uma interseção da psicanálise com a pediatria - Silvia Grebler Myssior (2007)
This essay consists of a psychoanalytic investigation about the diseases and psychosomatic manifestations that children and teenagers present, with clinicalconceptual emphasis in the psychosomatic phenomena, in the theoretical field of Psychoanalysis. The intersection between Psychoanalysis and pediatrics and pediatric specialties is proposed, aiming at the treatment of the patient. From the historicalsituation of the psychosomatic question, it is circumscribed in this research, our theorical mark. Distinct from the medical and psychiatrical approaches, where a genetic cause is attributed to the origin of the disturbances in psychological functions that are manifested in the body as psychosomatic, the limits to the mapped differences in the specific terrain of Psychoanalysis are determined here, that considers the body not as an organism, but as an expression of the unconscious, affected by the language. Starting from the psychoanalysts that traditionally have occupied themselves with the matter, this study falls on the thesis of Sigmund Freud and Jacques Lacan, passing by the theories of Donald Winnicott, and of how they approached the clinical aspects of thepsychosomatic disorder. The necessity to introduce the dimension of the instinct1 (impulse?) satisfaction, which, in these cases, seem to manifest itself through a specific joy, as is highlighted here. The concepts of: subject, great Other, body, instinct (impulse?), desire, joy and anguish, will be approached such as formulated by the above authors cited as references in this study. This essay is also reinforced by the writings ofa few analysts who, in current time, have been supporting the treatment of diseases and psychosomatic manifestations in the psychoanalytic practice. The fragments of the eight cases that compose this study have as an objective: to verify the hypothesis, reinstate the concepts and renew their postulates, through the Clinical Case Report Construction methods. Besides this, not free of some audacity, to incite upon the psychoanalytical and pediatric fields.